The Works of John Dryden, Volume XIV : Plays; The Kind Keeper, The Spanish Fryar, The Duke of Guise, and The Vindication - Dryden, John, 1631-1700 (Book collections on Project MUSE., 1992)
Kept women, comic clerics, and political schemers enliven the four plays in this volume of the California Dryden.